2018
DOI: 10.1007/s10620-018-5203-4
|View full text |Cite
|
Sign up to set email alerts
|

Both Full Glasgow-Blatchford Score and Modified Glasgow-Blatchford Score Predict the Need for Intervention and Mortality in Patients with Acute Lower Gastrointestinal Bleeding

Abstract: In patients with lower GI bleeding, both full GBS and modified GBS can predict the need for hospital-based interventions and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…[23] In addition, the GBS does not have the predictive value for endoscopic intervention. [24] A retrospective study [25] has shown that the mortality rates of high-risk patients with GBS >12 points could be reduced if these patients underwent endoscopic examination within 13 hours. Therefore, endoscopic examination should be performed as soon as possible in patients with a GBS >12 points.…”
Section: Discussionmentioning
confidence: 99%
“…[23] In addition, the GBS does not have the predictive value for endoscopic intervention. [24] A retrospective study [25] has shown that the mortality rates of high-risk patients with GBS >12 points could be reduced if these patients underwent endoscopic examination within 13 hours. Therefore, endoscopic examination should be performed as soon as possible in patients with a GBS >12 points.…”
Section: Discussionmentioning
confidence: 99%
“…Scores that do not require data on endoscopic findings specific to UGIB (pre-endoscopic scores) could be applied to not only UGIB but also LGIB; thus, they can be used to assess the risk of all GIB patients 7 . Indeed, Although the Glasgow-Blatchford score (GBS), clinical Rockall score (cRS), and AIMS65 scores, all of which are pre-endoscopic scores 3 5 , were initially designed for UGIB, some reports have indicated that these scores are also useful for the risk stratification of LGIB 10 13 . Recently, a new pre-endoscopic score, the ABC score was developed for predicting mortality in patients with overall GIB early after presentation, and showed high accuracy for both UGIB and LGIB 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The GBS is also an extensively investigated factor in the treatment of gastrointestinal bleeding. Although the GBS was actually developed for upper gastrointestinal bleeding, it reduced hospital-based interventions and mortality rates in LGIB as well[ 34 , 35 ]. Besides, we established GBS as a positive predictor in the demonstration of bleeding on angiography.…”
Section: Discussionmentioning
confidence: 99%